A Comparative Study on Business Performance through the Law of Attraction and Traditional Management Principles - Dhanani, Sunny (Digital Repository of Theses - SSBM Geneva, 2024)
This research endeavours to scrutinize and compare the efficacy of the Law of Attraction (LOA) against traditional management principles in shaping business performance. By juxtaposing the intuitive and psychological underpinnings of the LOA with the structured methodologies of conventional management, this thesis seeks to elucidate which approach yields superior outcomes in contemporary business scenarios. The Law of Attraction, a philosophical concept rooted in the belief that positive thoughts attract positive outcomes, has gained significant attention in various domains, from personal development to business strategies. This thesis delves into the application of the Law of Attraction principles in the context of customer retention. By exploring how businesses can harness the power of positive experiences and interactions to retain customers, this research aims to provide insights into innovative customer retention strategies. The Law of Attraction is a powerful technique that can be used in Business Management to improve employee and customer retention over the long term, establish a positive brand reputation, cultivate a positive mindset set and visualize goals, boost confidence, and enhance communication vi within the company. Furthermore, it can help businesses attract opportunities during tough economic times, reduce stress, and ultimately increase overall revenue. The findings of this research study have revealed how small product-based firms should fully acknowledge the value and sufficiency of customer retention, as a contributing factor in determining the longevity of the business. The findings have also demonstrated that small business leaders and managers must understand the importance of the Law of Attraction in formulating various retention approaches and methods, as tools to affirm and reiterate positive customer experiences, repeat purchasing behaviour, and invoke loyalty to the company thereby contributing to the revenue and profitability of the Business. The findings of this research study have also helped us with the psychology retaining of existing customers & attracting new ones, thereby reviving the direct relationship between customer satisfaction, & customer trust with a large pool of satisfied customers which tends to have a long-term competitive advantage and is more likely to sustain their profitability over a more extended period (Bhat & Darzi, 2016). To obtain substantial and adequate findings through analysis and data saturation, future researchers should consider expanding the population of their study by examining a larger sample. Additionally, researchers should aim to broaden the scope of the study and expand it to encompass all business sectors. By avoiding confining the scope and parameters of the data, the findings could reveal customized retention opportunities and implications for all markets and industries.